Penerapan Metode Quantum Learning Pada Pembelajaran Pendidikan Agama Islam - Siti nasim jf; Nurut Taufik (At-Tarbiyah Jurnal Pendidikan,Kebudayaan dan Keislaman, 2024)
The current development of education demands learning models that not only emphasize knowledge transfer, but also create meaningful learning experiences and foster character building, especially in Islamic Religious Education (PAI). The purpose of this article is to examine the effectiveness of implementing the Quantum Learning method in PAI instruction. This research employs a library research method by reviewing the latest scientific literature related to Quantum Learning and its application in PAI classrooms. The results of the discussion indicate that Quantum Learning is effective in improving cognitive learning outcomes, motivation, active participation, as well as the internalization of religious values and students' character through strategies such as TANDUR, simulations, and the use of visual media. However, the effectiveness of this method is strongly influenced by teacher readiness, the availability of supporting facilities, and institutional support. The conclusion of this study is that Quantum Learning can be an innovative and relevant alternative for PAI learning in the modern era, provided that teacher training and adequate facilities are available as supporting factors for its success.